Algorithms of Machines and Law:: Risks in Pattern Recognition, Machine Learning and Artificial Intelligence for Justice and Fairness - Losavio, Michael (Public Governance, Administration and Finances Law Review, 2021)
Pattern recognition, machine learning and artificial intelligence offer tremendous opportunities for efficient operations, management and governance. They can optimise processes for object, text, graphics, speech and pattern recognition. In doing so the algorithmic processing may be subject to unknown biases that do harm rather than good. We examine how this may happen, what damage may occur and the resulting ethical/legal impact and newly manifest obligations to avoid harm to others from these systems. But what are the risks, given the Human Condition?